2018
DOI: 10.1016/j.jadohealth.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Texting/Emailing While Driving Among High School Students in 35 States, United States, 2015

Abstract: Prevalence of TWD among US high school students varied by more than two-fold across states. TWD prevalence was higher in states with lower minimum learner's permit ages and in states where a larger percentage of students drove. Older age, white race/ethnicity, and other risky driving behaviors were associated with TWD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 32 publications
7
27
1
Order By: Relevance
“…Average TWD prevalence of 38% as reported by Li et al [10] among high school students is reasonably consistent with other reports of prevalence among adolescent and adults [5,7] and high enough to be considered normative behavior. Handheld phone use is legally restricted in nearly all states [11], although policies and enforcement vary and effects are largely unknown.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Average TWD prevalence of 38% as reported by Li et al [10] among high school students is reasonably consistent with other reports of prevalence among adolescent and adults [5,7] and high enough to be considered normative behavior. Handheld phone use is legally restricted in nearly all states [11], although policies and enforcement vary and effects are largely unknown.…”
supporting
confidence: 89%
“…Therefore, the prevalence of TWD is particularly high among young drivers, whose crash risk in general is higher than other age groups owing to inexperience, young age, risk taking, and other factors [9]. In this issue of the Journal of Adolescent Health, Li et al examined the prevalence of TWD reported by over 100,000 high school students in 36 states in the 2015 Youth Risk Behavior Survey [10]. Not surprisingly, TWD prevalence was greater among adolescents who also reported engaging in other risky behaviors, such as driving while intoxicated and seat belt non use.…”
mentioning
confidence: 99%
“…A similar categorization was consistent with a previously published study using YRBSs data on texting/emailing while driving. 35 The state status of handheld calling bans and young driver bans were classified as 1) the absence of a handheld calling ban and a young driver ban (no ban); 2) the absence of a handheld calling ban but an enacted young driver ban (young driver ban); and 3) the enactment of both a handheld calling ban and a young driver ban (concurrent bans). No YBRSs participating state had an enacted handheld calling ban but an absence of a young driver ban during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that teen driver cellphone use, varies by age, sex, race/ethnicity, and urban/rural status. 23,27,[35][36][37] For our study, urban/rural status was presented by the proportion of state's public school districts that were in rural areas, which was calculated by dividing the number of public school districts in rural areas by the total number of public school districts in that states. We categorized the district proportion into three groups by approximately equal tertiles (17%-50%; 51%-78%; 79%-90%).…”
Section: Methodsmentioning
confidence: 99%
“…Of note, texting while driving was the one transportation risk behavior that did not differ by academic achievement. One potential explanation is that although adolescents understand that texting while driving is unsafe, the perceived benefits of texting while driving and the motivations for engaging in the behavior often differ from other transportation risk behaviors and can outweigh the perceived risks for adolescents at the moment when they choose to do it (8,9).…”
Section: Discussionmentioning
confidence: 99%